2015
DOI: 10.1007/978-3-319-26410-3_26
|View full text |Cite
|
Sign up to set email alerts
|

LED Strips for Color- and Illumination-Based Emotion Regulation at Home

Abstract: An experimental setup for emotion regulation at home is introduced in this paper. The experimentation starts from the premise that changes in the ambience in terms of illumination and color are able to produce alterations in inhabitants' emotional state. The proposal uses RGB LED strips that are regulable in color and intensity to control the ambience. The full details of the assembly of a circuit that includes a microcontroller and a number of strips are provided. Afterwards, a novel approach for complex colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Participants of this study indicated that pink, red, orange and yellow maximized their feeling of joy, while sadness correlates with dark brown and gray. Ortiz-García-Cervigón et al [ 56 ] proposed an emotion regulation system at home, using RGB LED strips that are adjustable in colour and intensity to control the ambience. This study reveals that warm colours are rated as more tensed, hot, and less preferable for lighting, while cold colours are rated as more pleasant.…”
Section: Introductionmentioning
confidence: 99%
“…Participants of this study indicated that pink, red, orange and yellow maximized their feeling of joy, while sadness correlates with dark brown and gray. Ortiz-García-Cervigón et al [ 56 ] proposed an emotion regulation system at home, using RGB LED strips that are adjustable in colour and intensity to control the ambience. This study reveals that warm colours are rated as more tensed, hot, and less preferable for lighting, while cold colours are rated as more pleasant.…”
Section: Introductionmentioning
confidence: 99%